Integral formation at BNCC: reflections on Vocational and Technological Education (Research, Society and Development, 2022)
In this article we seek to analyze the reflexes of the National Curricular Common Base (BNCC) in professional and technological education. This teaching modality presupposes an ideal of integral formation, which underlies a conception of education whose objective is the development of the subject in the most varied dimensions of his existence with a view to understanding and (re)action to certain circumstances of life and of the world of work, allowing young people and adults to be and be in the world in a critical and conscious way. For this reflection, we carried out an exploratory study, which comprises the first stage of a broader investigation and focuses on the reading of theoretical texts on the subject. In this perspective, this reading of theoretical texts characterizes this study as a bibliographic survey. In this reflection, we conclude that the insertion of Transversal Contemporary Themes (TCT) in the curricular proposal constitutes a way to ensure integral formation.